Improving High Order Thinking Skills With Republic Polytechnics Singapore Lecturers Through Field Trip Implementation of Biochar On Soil In Pangambatan Village, Merek District, Tanah Karo Regency - Charloq (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
. Fieldtrip assistance for lecturers from the Republic Polytechnic of Singapore, and the Consulate-General of the Republic of Singapore Medan by lecturers and students of the University of North Sumatra to Pangambatan Village, Merek District, Karo Regency, as a form of applied scale learning directly in the field. The purpose of this field trip is to socialize the benefits of biochar technology as a soil and plant improver. In the implementation of this learning, an approach was taken using the Service Learning Method: It is a learning, teaching and reflection strategy that provides opportunities for lecturers and students to apply biochar technology and serve farmers and communities, by combining learning in lectures with the needs and problems that exist in the soil and plants and the environment in the form of sustainable agriculture in farming communities. Socialization and technology on biochar, how to make an application in the field were delivered by USU lecturers and students. The next meeting continued in the form of discussions in the seminar room of the Taman Simalem Resort Hotel which was attended by participants and Indonesian Geology experts. The meeting was followed by a discussion in the Seminar Room of Taman Simalem Resort Hotel attended by the participants. The field trip produced and honed the ability of high order thinking skills (HOTS), lecturers, students of Republic Polytechnic of Singapore, and Consulate-General of The Republic of Singapore Medan, Geology Experts and Plasma Farmers, know and understand the importance of biochar for agricultural soils for soil improvement in terms of physical, chemical and biological soil to be healthy and increase crop production. The results of investigations in the field some farmers want to apply biochar on their land in the next planting season and will form a biochar user farmer group.